Electronic Learning Material of Newton’s Laws with Kvisoft Flipbook Maker to Improve Learning Outcomes of Students - Asrizal Asrizal; Dona Fitri Ayu; Vivi Mardian; Festiyed Festiyed (Jurnal Penelitian Pendidikan IPA, 2022)
In the world of education, teachers can use technology in learning activities in learning material. The fact found in schools is that the learning material used by students are still low in the use of technology. This indirectly has an impact on student learning outcomes which are still low. One solution that can be done is to apply Newton's law electronics learning material with Kvisoft Flipbook. This study aimed to improve the learning outcomes of class X students of SMAN 1 Payakumbuh. This research is a quasi-experiment with a randomized posttest only control group design. The sampling technique used purposive sampling with random cluster sampling. The data collection instrument consisted of a written test sheet for the knowledge aspect, an observation sheet for the attitude aspect, and a performance appraisal sheet for the skills aspect. From the results of data analysis, it can be stated that applying Newton's law electronics learning material with Kvisoft Flipbook Maker can improve learning outcomes in the knowledge, attitudes, and skills of class X students of SMAN 1 Payakumbuh with a 95% confidence level.